Differenzialdiagnostik manualmedizinischer Syndrome bei unteren Rückenschmerzen unter Einbeziehung osteopathischer Verfahren - Buchmann, J.; Arens, U.; Harke, G.; Smolenski, U. C.; Kayser, R. (Sportverletzung · Sportschaden, 2012)
The differential diagnostic evaluation of painful functional disorders of the lumbosacral and lumbopelvic region, i. e. the so-called "low back pain” is very extensive, but is often reduced to the question of chronicity. The manual medical diagnosis can make a valuable contribution in such cases for determination of structural and functional pathology. Early application of manual medical therapies seems to be effective for peracute complaints. The mobilization of restrictions of the pelvic visceral attachments should be included. In the following review manual medical syndromes are presented that summarize the findings from the musculoskeletal and visceral system. This is intended to facilitate the primary differential diagnostic evaluation, as well as treatment planning. The combination with osteopathic methods is very profitable. A necessary specialist differential diagnosis remains essential.